Customer Acceptance Analysis of Customer Relationship Management (CRM) Systems in Automotive Company using Technology Acceptance Model (TAM) 2 - Caesar Wenston Ngangi, Stephano; Joko Santoso, Albertus (Indonesian Journal of Information Systems, 2019)
The technological era in business competition requires creativity and innovation to create a successful company. CRM (Customer Relationship Management) is a system that aims, among others, to provide improving relations between the company and customers, so that the realization of integrated information is used to produce optimal services and obtain useful customer information so that customer needs can be met and encouraged to loyalty. In addition, CRM can be useful to improve efficiency and reduce operational costs of PT. Hasjrat Abadi (Tendean Branch). To support the success of PT. Hasjrat Abadi (Tendean Branch), this study will examine a CRM system to be applied to PT. Hasjrat Abadi (Tendean Branch) by integrating it into the Technology Acceptance Model (TAM) as a model that can be analyzed and understood so that later it can influence customers in the use of technology as an information system by using informational system variables. In this research, user acceptance has been reviewed based on 4 variables in TAM itself. PT. Hasjrat Abadi (Tendean Branch) has a problem where there is still a lack of customer demand for TOYOTA products. Therefore, the implementation of the TAM system for CRM will be pursued so that it can identify the customers of PT. Hasjrat Abadi (Tendean Branch) Manado who want to buy products from PT Hasjrat Abadi (Tendean Branch) Manado, and increase the selling value of the product.